Nancy clancy, super sleuth ebook Nancy clancy, super sleuth. - O'Connor, Jane (Nancy Clancy, 2012)
For young readers who grew up with the bestselling Fancy Nancy picture books, Nancy Clancy is now starring in her own chapter books! In this first in a series of delightful chapter books, Fancy Nancy takes on the role of detective. When one of Nancy's classmate's most treasured possessions disappear from school, it's up to detective Nancy to solve the mystery and save the day. With the help of her friend Bree, she follows the clues to an unexpected source. Fans of Nancy Drew's Clue Crew will be among the readers happy to see a new Nancy join the ranks of super sleuths!